The Factors Related to Musculoskeletal Disorders of Rice Milling Workers in Lembor District, West Manggarai - Agnes Alvionita Ance; Noorce Christine Berek; Yuliana Radja Riwu (Lontar : Journal of Community Health, 2021)
Musculoskeletal disorders are usually used to describe a condition such as an injury, pain, or abnormality in the skeletal muscle system which consists of nerve tissue, muscles, bones, ligaments, tendons, and joints. Musculoskeletal disorders are a disease that is often experienced or felt by workers due to work attitudes and work positions that are not ergonomic as well as long working hours and workloads that are often received by workers. This study aims to determine the factors that cause musculoskeletal disorders in rice mill workers in Lembor District. This study used an analytical study with a cross-sectional study design. The research location is in a rice mill in Lembor District, and the data were conducted from January to August 2020. The subjects in this study were 60 rice mill workers. Dependent variables: musculoskeletal disorders, independent variables age, years of service, length of work, work position, and workload. This study uses a simple linear regression test. The results of statistical tests showed that the variable age was associated with musculoskeletal disorders (p-value = 0.013), the working period variable was related to musculoskeletal disorders (p-value = 0.000), the length of work variable was related to musculoskeletal disorders (p-value = 0.012), work position was related to musculoskeletal disorders. Musculoskeletal disorders (p-value = 0.049), and workload not associated with musculoskeletal disorders (p-value = 0.538). It is hoped that rice mill workers can have their health checked if they experience disorders in all parts of their bodies and pay attention to their body position during work.